Chairside Light-Curing as a Feasible Alternative to Laboratory Polymerization for Indirect Composite Resins: A Performance-Based In Vitro Study - Abdullah, Ammar (2026)
Indirect composite resins are widely used for extensive restorations due to their favorable mechanical properties; however, their polymerization typically requires laboratory light-curing devices, which may increase treatment time and cost and are not always readily available in routine clinical settings. High-intensity chairside light-curing units have been proposed as a potential alternative for extraoral polymerization. To evaluate, using a performance-based comparative approach under standardized post-curing conditions, whether chairside light-curing units can achieve mechanical properties comparable to those obtained with laboratory light curing in indirect composite resins. Indirect composite resin blocks (Twiny) were fabricated using a standardized mold (6×6×4 mm) and randomly allocated into three groups (n=20): laboratory light curing (control), chairside light curing for 20 s, and chairside light curing for 40 s. All specimens underwent thermal post-curing at 115 °C for 15 min to standardize polymer network maturation. Surface microhardness and compressive strength were evaluated. Data were analyzed using one-way ANOVA followed by the LSD post hoc test (p<0.05). Chairside light-curing groups demonstrated significantly higher surface microhardness values compared with the laboratory-curing group (p<0.05), with no significant difference between 20 s and 40 s exposures (p>0.05). Compressive strength values did not differ significantly among groups (p>0.05), indicating comparable bulk mechanical performance. Within the limitations of this in vitro study, chairside light curing achieved mechanical performance comparable to laboratory polymerization for indirect composite resins when combined with standardized thermal post-curing. These findings suggest that chairside light-curing may represent a clinically practical alternative for extraoral polymerization in settings where laboratory devices are unavailable, although long-term in vivo performance requires further investigation.